2015
DOI: 10.18801/jbar.030115.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth and Yield Characteristics of BARI Tomato Varieties

Abstract: An experiment was conducted at Agronomy Farm of the Sher-e-Bangla Agricultural University, Dhaka to study growth and yield responses of tomato varieties. Experiment consisted of four varieties, viz. BARI Tomato-4 (V 1), BARI Tomato-5 (V 2), BARI Tomato-7 (V 3) and BARI Tomato-9 (V 4) using Randomized Complete Block Design with three replications. Tallest plant (101.3 cm), maximum number of leaves (114.1/plant) and maximum number of branches (10.0/plant) was found from BARI Tomato-7. While maximum number of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Similar results were also found by Biswas et al, (2015) who had reported variable performance for this character may be due to variable response of the different cultivar in different environments. Among all the environments, maximum value was recorded in treatment E4 (92.27 g) followed by E3 and E2.The data showed that foliar spray of 2, 4-D significantly increased the average fruit weight in E3 than E1 in open field condition.…”
Section: Average Fruit Weightsupporting
confidence: 88%
“…Similar results were also found by Biswas et al, (2015) who had reported variable performance for this character may be due to variable response of the different cultivar in different environments. Among all the environments, maximum value was recorded in treatment E4 (92.27 g) followed by E3 and E2.The data showed that foliar spray of 2, 4-D significantly increased the average fruit weight in E3 than E1 in open field condition.…”
Section: Average Fruit Weightsupporting
confidence: 88%
“…. Variation in number of leaves/ 10cm shoot and leaves/plant was also observed previously in rose (Ahmad et al, 2011; Manjula, 2005; Paramagoudar, 2010), carnation (Gharge et al, 2011; Tarannum et al, 2014; Pralhad, 2009), gerbera (Hossain et al, Corresponding author email: jamal4@yahoo.com (Jamal Uddin, A. F. M.) eISSN: 2312-7945, © Shahrin et al 2015, Research paper 2015; Mehraj et al, 2014b; Jamal Uddin et al, 2014a; Mahmood et al, 2013; Chobe et al, 2010;Kumari et al, 2010;Pattanashetti, 2009;Shruti et al, 2013), strawberry(Ahsan et al, 2014;Hossan et al, 2013), tomato(Biswas et al, 2014) and chilli(Mehraj et al, 2014c).…”
mentioning
confidence: 99%
“…It is a good appetizer having pleasing test. Tomato juice contains lycopene one of the most powerful antioxidant and vitamin C which are most beneficial to human beings [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%